STUDI KASUS : PROGRAM FISIOTERAPI PADA KASUS CEREBRAL PALSY ATAKSIA DI KLINIK INTAN FISIOTERAPI ANAK - Ulfah Zulfahmi; Umi Budi Rahayu; Intan Herlinawati (LPPM STIKES Siti Hajar dan Insight Power, 2022)
Introduction: Cerebral Palsy (CP) is a neuromotor disorder that affects the development of a movement, muscle tone, and posture caused by abnormalities in the developing part of the brain. Ataxic cerebral palsy is one of the most common types of cerebral palsy. The characteristics are by producing abnormal movement patterns due to disturbances in the cerebellum where the function of the cerebellum is as a center for controlling balance, coordination, and muscle tone. Physiotherapy can improving functional abilities and conditions with a Multidisciplinary approach (MDT), to reduce functional limitation, psychological limitations, and improve quality of life in children. Physiotherapy focuses on function, movement, and optimal use of the child's potential. Objective: to determine the effectiveness of the physiotherapy program in cases of cerebral palsy ataxia. Methods: The study design used a single-subject research conducted on 18-month-old patients with cerebral palsy. The interventions used were patterning, exercise therapy, atlantooccipital mobilization, and standing frame exercise which were performed 3 times a week for 4 weeks. Results: Evaluation was carried out 2 times using Gross Motor Functional Measurement (GMFM). After doing physiotherapy, it was found that there was an increase in motor functional activity as measured by the T1 result of 49.4%; T2 52.7%; and T3 59.7%. Conclusion: From the results, there was an increast in motor functional abilities after being given physiotherapiprograms for 4 weeks.Keywords: Cerebral Plasy Ataxia, GMFM, Patterning, Exercise, Standing Frame, Atlanto Occipitalis Mobilization